The control of Latin American trypanosomiasis - Marsden, Philip Davis (1997)
The author presents his personal point of view on the present situation of Chagas' disease control in Latin America countries. He compares the situation with African trypanosomiasis. He comments on the existence of cases in other Continents. He emphazises the success of the fighting against domiciliated triatomine bugs by using residual inseticides. He discusses other forms of Trypanosoma cruzi transmission.